The prevalence of anemia in pregnant women in the 10 priority villages for stunting control in Sumedang district, West Java: a community-based survey - Nainggolan, Sudung; Siagian, Forman E. (International Journal Of Community Medicine And Public Health, 2019)
Background: Anemia in pregnant women possessed potential harm to mother and child. There were 48.9% of pregnant women suffering from anemia and 40% of women of childbearing age also suffer from anemia. Incidence of anemia among pregnant women is prominent health problems especially in developing countries such as Indonesia. The aim of the present study is to determine the prevalence of anemia among pregnant women in relation to infection of Soil-Transmitted Helminthes (STH) and Serum Iron deficiency in 10 priority villages for stunting control set by the government in Sumedang district, West Java. Methods: This is a community-based survey. Hemoglobin concentration was obtained from finger prick blood test. Containers for stool specimens and anal swabs were given to each woman at the time of hemoglobin fingerpick blood test showed positive results for anemia. Data were analyzed using SPSS software. Results: Out of 209 pregnant women examined we found 39 pregnant women (18.7%) suffering from anemia. Followed by serum iron analysis we found 23.3% of the total number of pregnant women with iron deficiency. On microscopic examination of fecal specimens and anal swabs we found no worm eggs or larvae in the specimens examined. Conclusions: Hemoglobin examination found that there were 18.7% pregnant women with anemia and 23.3% suffering iron deficiency. Microscopic examination of fecal samples and anal swabs in pregnant women with anemia showed neither STH eggs nor larvae.